Buck-Boost DC-DC Converter Control by Using the Extracted Model from Signal Flow Graph Method - Leila MOHAMMADIAN; Ebrahim BABAEI; Mohammad Bagher BANNAE SHARIFIAN (International Journal of Applied Methods in Electronics and Computers, 2015)
In this paper, the signal flow graph technique and Mason gain formula are applied for extracting the model and transfer functions from control to output and from input to output of a buck-boost converter. In order to investigate a controller necessity for the converter of assumed parameters, the frequency and time domain analysis are done and the open loop system characteristics are verified and the needed closed loop controlled system specifications are determined. Finally designing a controller for the mentioned converter system based on the extracted model is discussed. Then, a modern control design method is employed for regulator design. For this purpose, a full state feedback control for pole placement is applied. The simulation results are used to show the performance of the proposed modeling and regulation method.